1989
DOI: 10.1056/nejm198910193211602
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Inhaled Furosemide on Allergen-Induced Early and Late Asthmatic Reactions

Abstract: The movement of ions and water across the membranes of bronchial cells is part of the control of the bronchial obstructive response to physical stimuli. In a double-blind, randomized, crossover study, we compared the effect of an aerosol of the loop diuretic furosemide with that of a placebo on the early (within 60 minutes) and late (4 to 12 hours) asthmatic responses to a specific inhaled allergen. We studied 11 subjects with mild allergic asthma, who had both early and late asthmatic responses to a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
2

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(80 citation statements)
references
References 19 publications
1
77
2
Order By: Relevance
“…Frusemide has been shown to have the capacity to prevent the release of inflammatory mediators, such as leukotrienes, from passively-sensitized human lung in vitro [23]. However, we found no evidence that frusemide was active in reversing the reduced clearance observed in asthmatic patients, even at a dose that is known to inhibit allergen-induced acute response in asthmatics [1,24]. Studies of the protective effect of frusemide against airway challenges have been performed within 30 min of challenge, but in a study of its inhibitory effect against cough challenges, we found an effect lasting for up to 3 h [25].…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Frusemide has been shown to have the capacity to prevent the release of inflammatory mediators, such as leukotrienes, from passively-sensitized human lung in vitro [23]. However, we found no evidence that frusemide was active in reversing the reduced clearance observed in asthmatic patients, even at a dose that is known to inhibit allergen-induced acute response in asthmatics [1,24]. Studies of the protective effect of frusemide against airway challenges have been performed within 30 min of challenge, but in a study of its inhibitory effect against cough challenges, we found an effect lasting for up to 3 h [25].…”
Section: Discussioncontrasting
confidence: 82%
“…There were no statistically significant differences between the two runs for FEV 1 and Vmax 50 within each group. Alveolar deposition for the placebo and frusemide were 44±4 vs 45±3%, respectively, for the asthmatic group; and 66±7 vs 57±9% respectively, for the healthy group.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Inhaled furosemide was used with some success to treat breathlessness asthma patients and healthy volunteers whose breathlessness was induced (Bianco et al, 1989, Nishino et al, 2000. This finding led to inhaled furosemide being evaluated in cancer patients.…”
Section: Furosemidementioning
confidence: 99%
“…Eur Respir J., 1994Respir J., , 7, 1825Respir J., -1829 Inhalation of frusemide and, to a lesser extent other loop diuretics, inhibits the bronchoconstriction induced by allergens and by several nonallergic stimuli, such as exercise, hypo-and hypertonic aerosols, cold air, metabisulphite and adenosine [1,2]. Although frusemide protects against the late asthmatic reaction up to 12 h after allergen exposure [3], the protective effect against ultrasonically-nebulized distilled water and sodium metabisulphite is relatively short-lived, lasting for 1-2 h [4,5]. Bronchoconstriction induced by inhaled acetylsalicylic acid (ASA) in aspirin-sensitive asthmaticshas a relatively long time course, peaking around the second hour and usually lasting more than 4 h after exposure [6,7].…”
mentioning
confidence: 99%